2018
DOI: 10.1016/j.molcel.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Modulation of RNA Splicing with a CRISPR-Guided Cytidine Deaminase

Abstract: Highlights d TAM efficiently modulates four types of splicing in their native genomic context d Genetic modulation of RNA splicing elucidates functions of splicing isoforms d TAM enables both loss-and gain-of-function studies of splicing events d TAM corrects the open reading frame of 99.9% of DMD transcripts in patient iPSCs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(105 citation statements)
references
References 49 publications
0
98
0
1
Order By: Relevance
“…34,35 Correction of mutations in DMD cells could be achieved by CT followed by differentiation to muscle cells and their injection in the muscles, an option that has been used by several researchers in muscle pathology. 27,33,[36][37][38] The only needed additional step to the protocol used herein is the inactivation, before retro-MMCT fusion, of the HPRT gene on the endogenous X chromosome by CRISPR technology, allowing the use of HAT selection after retro-MMCT. We have recently shown the feasibility of this step by correcting the genetic defect in iPSCs from a mouse model of the X-linked CGD.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Correction of mutations in DMD cells could be achieved by CT followed by differentiation to muscle cells and their injection in the muscles, an option that has been used by several researchers in muscle pathology. 27,33,[36][37][38] The only needed additional step to the protocol used herein is the inactivation, before retro-MMCT fusion, of the HPRT gene on the endogenous X chromosome by CRISPR technology, allowing the use of HAT selection after retro-MMCT. We have recently shown the feasibility of this step by correcting the genetic defect in iPSCs from a mouse model of the X-linked CGD.…”
Section: Discussionmentioning
confidence: 99%
“…Yuan et al (2018) used a catalytically deficient version of Cas9 (dCas9) fused to a cytidine deaminase to specifically edit single DNA bases [97]. Applying this to eliminate the exon 50 donor splice site in exon 51-deleted patient hiPSCs, they achieved exon 50 skipping and dystrophin production in iCMs.…”
Section: Studies Using Human Ipsc Modelsmentioning
confidence: 99%
“…The single base‐editing technology has been used not only in mice to model human diseases but also directly in human cells (G. Li et al, ; Liang, Ding et al, ; Yuan et al, ; Zeng et al, ; Zhou et al, ). The CBE3 and SaKKH‐BE3 (PAM is NNNRRT) systems have been used to mutate one or three genes simultaneously in human trigeminal zygotes with very high efficiency, indicating that CBE3 induces near perfect gene editing in the target site with extremely low off‐target mutagenesis and indel mutations in human cells (G. Li et al, ; Zhou et al, ).…”
Section: Applications Of Crispr‐mediated Base Editingmentioning
confidence: 99%
“…RNA splicing is a critical mechanism by which to modify transcriptome, and its dysregulation is associated with many human diseases. Intriguingly, a report has shown that TAM can be used to modulate RNA splicing by editing splice sites (Yuan et al, ). Thus, the CRISPR‐guided cytidine deaminase provides a versatile genetic platform to modulate RNA splicing and correct mutations associated with aberrant splicing in human diseases (Yuan et al, ).…”
Section: Applications Of Crispr‐mediated Base Editingmentioning
confidence: 99%